Nodular sclerosing adenosis: Case report - Doğan, Emrah; Tekin, Leyla; Çelik, Serkan Yaşar; Polat, Murat; Doğan, Marwa Mouline (Journal of Surgery and Medicine, 2019)
Sclerosing adenosis (SA) is a benign proliferative type of breast disease affecting the acinar, myoepithelial and connective tissue in the terminal ductal lobular units. Sclerosing adenosis, which gives a nodular appearance on mammography and ultrasonography, is defined as nodular sclerosing adenosis (NSA). NSA is an atypical radiological presentation of SA. Such lesions may arouse suspicions about the reliability of the diagnosis when they receive a diagnosis of SA in the needle biopsies. Therefore, it should be kept in mind that SA may rarely be seen as a nodular mass.